REMOTE SENSING AND GIS IN URBAN SPRAWL AND ARABLE LAND LOSS ANALYSIS: A CASE OF BAMAKO DISTRICT IN MALI - Renzong, Ruan; Ru, An; Keita, Moussa Aliou (International Journal of Research -GRANTHAALAYAH, 2018)
This paper analyzes the impacts of urban sprawl on arable land loss in Bamako district from 1990 to 2018 by using remote sensing and geographic information science capabilities. The analysis was based on satellite images classification of Landsat Thematic Mapper (TM) 1990, 2000, Landsat Enhanced Thematic Mapper Plus (ETM+) 2010, Landsat 8 Operational Land Image and Thermal Infrared Sensor (OLI/TIRS) image for 2018 to show land use and cover changes, in particular arable land loss. The results showed a significant evolution of land use and land cover and important arable land loss. From 1990 to 2018, the construction has increased by 73.06% while arable land decreased by 55.39%. The results also revealed that urban sprawl has exceeded the administrative boundaries of Bamako and is continuing in neighboring municipalities. This article recommends the adoption of legal measures, the development of urban development master plan, and close collaboration with different actors involve in land management for better management of arable land and urban sprawl. Finally, for a global understanding of the phenomenon in the urban area of Bamako, the study suggests a more in-depth study of a global approach to urban sprawl in the Bamako district, taking into account the surrounding rural communes, which affect today greatly the urban sprawl of Bamako.